Fluorinated zinc phthalocyanine as donor for efficient vacuum-deposited organic solar cells - Meiss, J; Merten, A; Hein, M; Schuenemann, C; Schäfer, S; Tietze, M; Uhrich, C; Pfeiffer, M; Leo, K; Riede, M (Wiley, 2012)
Efficient single bulk heterojunction organic solar cells based on blends of a fluorinated zinc phthalocyanine as electron donor and fullerene C60 as electron acceptor are reported. In comparison to the commonly used absorber zinc phthalocyanine, the fluorination of the molecule to F4ZnPc leads to an increase in ionisation potential and subsequently to an improvement of about 170 mV in the open circuit voltage of organic solar cells, while the short circuit current density and fill factor remain nearly unchanged. Similar to ZnPc:C60-based devices, the device characteristics of F4ZnPc:C60 solar cells can be further enhanced by improving the blend layer morphology by substrate heating during deposition. F4ZnPc is an efficient donor material that can achieve a 4.6% power conversion efficiency in single heterojunction organic solar cells. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.